Obstructive Pneumonia due to Unknown Eosinophilic Mucoid Impaction of Bronchi: a Case Report - Jung, Jae-Wan; Hwang, Ki-Eun; Sohn, Ki-Chang; Lim, Byung-Hun; Cho, Kyung-Hwa; Kim, Hak-Ryul; Jeong, Eun-Taik (The Korean journal of medicine, 2015)
We report an unusual case of obstructive pneumonia due to an unknown eosinophilic mucoid impaction of the bronchi (MIB). A 54-year-old woman visited our hospital for investigation of abnormal shadows visible on a chest radiograph. Chest computed tomography and bronchoscopic examination revealed pneumonia due to MIB. Histopathological examination of biopsied mucosal tissue revealed extensive eosinophilic infiltration. With the exclusion of medical diseases that can cause eosinophilia, pneumonia due to eosinophilic mucoid impaction of the bronchi was diagnosed. The cause of the eosinophilia remained unknown. The pneumonia and mucoid impaction resolved after oral steroid therapy. KCI Citation Count: 0